PEMBUATAN LEMBAR KERJA MAHASISWA BERBASIS INKUIRI PADA MATERI SENYAWA FLAVONOID UNTUK MAHASISWA - Fania, Ririn Putri; Sahputra, Rachmat; Muharini, Rini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the feasibility and response of students to Student Worksheets (LKM)Â  Inquiry Based on Flavonoid Material based on the results of expert tests (expert judgment) and field trials which consisted of initial field trials and main field trials. This research took the form of research and development (R&D) which adopted from Borg & Gall development model. The subject of this study was an inquiry-based student worksheet that was tested on a third year Chemistry Education FKIP students at Tanjungpura University who had taken a course in Natural Chemistry Product. The results of the data analysis showed that inquiry-based student worksheets were very appropriate to be used in learning process in terms of content, presentation, linguistic, and graphic viability at 94.44%, 95%, 86.67%, and 90.44%, respectively. While the response of students to student worksheets was very high in the initial field trials of 84.96%, and in the main field trials of 88.73%.Â Keywords: Development, Flavonoids, Inquiry, Student WorksheetsÂ